A lithium iron manganese phosphate coated ternary composite material, a preparation method and application thereof

CN116598442BActive Publication Date: 2026-11-03EVE POWER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310328829.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2026-11-03
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

When lithium manganese iron phosphate is directly blended with ternary materials, the slurry dispersion is poor, resulting in insufficient conductivity, rate performance, and cycle performance.

Method used

The composite material employs a ternary core and a lithium manganese iron phosphate coating layer, both of which are doped with the rare earth element dysprosium to form an integral structure, improving the homogeneity, dispersibility and conductivity of the material, and enhancing structural stability through the use of dysprosium.

Benefits of technology

Excellent rate performance and cycle performance of composite materials were achieved, conductivity and homogenization dispersion were improved, and the overall performance of the battery was enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004154182930000141
    Figure BDA0004154182930000141
  • Figure BDA0004154182930000151
    Figure BDA0004154182930000151
Patent Text Reader

Abstract

The application provides a lithium manganese iron phosphate coated ternary composite material and a preparation method and application thereof. The composite material comprises a ternary inner core and a lithium manganese phosphate coating layer coated on the surface of the inner core; and dysprosium elements are doped in the ternary inner core and the lithium manganese phosphate coating layer. The composite material provided by the application comprises a ternary inner core and a lithium manganese phosphate coating layer coated on the surface of the inner core, has good homogenate dispersity, and the ternary inner core and the lithium manganese phosphate coating layer are both doped with rare earth dysprosium elements, so that the composite material has high conductivity and excellent rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology and relates to a lithium manganese iron phosphate coated ternary composite material, its preparation method and application. Background Technology

[0002] In recent years, with the booming development of the new energy industry, especially the rapid development of electric vehicles, the requirements for cycle stability and specific capacity of power batteries have become increasingly stringent. Among many cathode material systems, lithium manganese iron phosphate has better safety performance than ternary lithium batteries, higher energy density than lithium iron phosphate, and significant cost advantages, making it increasingly favored by cell manufacturers and OEMs.

[0003] However, the olivine crystal structure of lithium manganese iron phosphate (LMFP) results in poor conductivity and rate performance. Furthermore, the Jahn-Teller effect occurs due to the valence change of manganese, leading to manganese ion dissolution and increased battery polarization. Manganese ion deposition on the negative electrode surface damages the SEI layer structure, causing capacity loss and poor cycle performance. Combining LMFP with carbon materials can improve performance. CN110247044A discloses an in-situ graphene-composite LMFP cathode material and its preparation method. Graphene has excellent conductivity, which can improve the conductivity of the composite material; however, the ionic conductivity of the material is not significantly improved. CN110323434B discloses a method for preparing a LMFP-carbon composite material and the LMFP-carbon composite material itself. This patent combines LMFP with carbon materials, which also improves the conductivity of LMFP, but the ionic conductivity of LMFP is difficult to improve, resulting in poor cycle performance.

[0004] Blending ternary cathode materials into lithium manganese iron phosphate (LFP) can simultaneously improve its conductivity, rate performance, and cycle performance. CN104300123B discloses a hybrid cathode material, a cathode sheet using this material, and a lithium-ion battery. This hybrid cathode material comprises the following components in parts by weight: 50-90 parts of nickel-cobalt-manganese ternary material and 10-50 parts of lithium manganese iron phosphate. This patent combines the high-energy-density nickel-cobalt-manganese ternary material with the high-safety lithium manganese iron phosphate. However, directly blending lithium manganese iron phosphate and ternary materials presents challenges in the homogenization process and results in poor slurry dispersion.

[0005] Therefore, there is an urgent need to develop a composite material of lithium manganese iron phosphate and ternary materials to solve the problems of poor homogenization and dispersibility of the mixed materials of lithium manganese iron phosphate and ternary materials, as well as poor conductivity, rate performance and cycle performance compared with pure lithium manganese iron phosphate. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a ternary composite material coated with lithium manganese iron phosphate, its preparation method, and its applications. The composite material provided by the present invention comprises a ternary core and a lithium manganese iron phosphate coating layer on the surface of the core. It exhibits good homogeneity and dispersibility. Furthermore, both the ternary core and the lithium manganese iron phosphate coating layer are doped with the rare earth element dysprosium, resulting in high conductivity and excellent rate performance and cycle performance of the composite material.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a lithium manganese iron phosphate coated ternary composite material, the composite material comprising a ternary core and a lithium manganese iron phosphate coating layer covering the surface of the core;

[0009] Both the ternary core and the lithium manganese iron phosphate coating are doped with dysprosium.

[0010] This invention provides a ternary composite material coated with lithium manganese iron phosphate. The ternary core and the lithium manganese iron phosphate coating layer are integrated into the composite material, resulting in good homogeneous dispersion. At the same time, the doping of the rare earth element dysprosium into the ternary core and the lithium manganese iron phosphate coating layer not only solves the problems of poor conductivity and high self-discharge of pure lithium manganese iron phosphate, but also effectively improves the structural stability of the composite material by doping with the rare earth element dysprosium, enabling the composite material to exhibit excellent rate performance and cycle performance.

[0011] Preferably, the ternary core comprises a nickel-cobalt-manganese ternary cathode material doped with dysprosium and / or a nickel-cobalt-aluminum ternary cathode material doped with dysprosium.

[0012] Preferably, the mass ratio of the ternary core to the lithium manganese iron phosphate coating layer is (0.1-0.3):(0.7-0.9), wherein the range of the ternary core (0.1-0.3) can be, for example, 0.1, 0.15, 0.2, 0.25 or 0.3, and the range of the lithium manganese iron phosphate coating layer (0.7-0.9) can be, for example, 0.7, 0.75, 0.8, 0.85 or 0.9.

[0013] Preferably, the thickness of the lithium manganese iron phosphate coating layer is 0.1-0.5 μm, for example, it can be 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm.

[0014] Preferably, the dysprosium content in the lithium manganese iron phosphate coating is 1-3% by mass, for example, it can be 1%, 1.5%, 2%, 2.5% or 3%, etc.

[0015] Preferably, the dysprosium content in the ternary nucleus is 1-3%, for example, it can be 1%, 1.5%, 2%, 2.5% or 3%, etc.

[0016] In this invention, if the dysprosium content in the lithium manganese iron phosphate coating layer and the ternary core is too low, the dysprosium will not be able to play a role in stabilizing the crystal structure of the cathode material, making it difficult to improve the first-cycle coulombic efficiency of the composite material; if the dysprosium content in the lithium manganese iron phosphate coating layer and the ternary core is too high, too much dysprosium will hinder lithium-ion insertion and extraction, increasing the impedance of the material.

[0017] Secondly, the present invention provides a method for preparing the lithium manganese iron phosphate-coated ternary composite material described in the first aspect, the method comprising:

[0018] (1) Prepare lithium manganese iron phosphate precursor and ternary precursor respectively:

[0019] The method for preparing the ternary precursor includes: mixing a nickel source, a cobalt source, a manganese source, a solvent, and an alkaline solution, co-precipitating the mixture to obtain a precipitate, and calcining the precipitate to obtain the ternary precursor.

[0020] (2) The lithium manganese iron phosphate precursor, the ternary precursor, the lithium source and the dysprosium source are mixed and sintered to obtain the lithium manganese iron phosphate coated ternary composite material.

[0021] It should be noted that the preparation of lithium manganese iron phosphate precursor and the preparation of ternary precursor are not sequential in terms of time. The lithium manganese iron phosphate precursor can be prepared first, or the ternary precursor can be prepared first, or both lithium manganese iron phosphate precursor and ternary precursor can be prepared simultaneously.

[0022] In this invention, if the precipitate in step (1) is not calcined, the material cannot be formed, and the precipitate contains a large number of water molecules and some impurities, which directly affect the performance of the cathode material.

[0023] Preferably, the method for preparing the lithium manganese iron phosphate precursor includes: mixing a manganese source, an iron source and a phosphorus source, and sintering to obtain the lithium manganese iron phosphate precursor.

[0024] Optionally, in the method for preparing the lithium manganese iron phosphate precursor, the manganese source includes at least one of MnSO4, Mn(NO3)2 and MnCl2.

[0025] Optionally, in the method for preparing the lithium manganese iron phosphate precursor, the iron source includes at least one of FeSO4, Fe(NO3)2 and FeCl2.

[0026] Optionally, in the method for preparing the lithium manganese iron phosphate precursor, the phosphorus source includes H3PO4.

[0027] Preferably, in the method for preparing the lithium manganese iron phosphate precursor, the molar ratio of the manganese source, iron source and phosphorus source is (0.5-0.7):(0.3-0.5):1, wherein the range of manganese source selection (0.5-0.7) can be, for example, 0.5, 0.55, 0.6, 0.65 or 0.7, and the range of iron source selection (0.3-0.5) can be, for example, 0.3, 0.35, 0.4, 0.45 or 0.5.

[0028] Preferably, in the method for preparing the lithium manganese iron phosphate precursor, the sintering temperature is 250-350℃, for example, it can be 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃ or 350℃, etc.

[0029] Preferably, in the method for preparing the lithium manganese iron phosphate precursor, the sintering time is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.

[0030] Preferably, in the method for preparing the lithium manganese iron phosphate precursor, the sintering atmosphere is a reducing atmosphere, and the gases in the reducing atmosphere include, but are not limited to, argon and hydrogen.

[0031] Optionally, in the method for preparing the ternary precursor, the nickel source includes Ni(NO3)2·6H2O and / or Ni(SO4).

[0032] Optionally, in the method for preparing the ternary precursor, the cobalt source includes Co(NO3)2·6H2O and / or CoSO4.

[0033] Optionally, in the method for preparing the ternary precursor, the manganese source includes Mn(CH3COO)2·4H2O and / or MnSO4.

[0034] Preferably, in the method for preparing the ternary precursor, the molar ratio of the nickel source, cobalt source and manganese source is (5-7):1:(2-4), wherein the range of the nickel source (5-7) can be, for example, 5, 5.5, 6, 6.5 or 7, and the range of the manganese source (2-4) can be, for example, 2, 2.5, 3, 3.5 or 4.

[0035] Preferably, in the method for preparing the ternary precursor, the mixed raw materials further include at least one of sodium nitrite solution, sodium persulfate (APS) solution and polyvinylpyrrolidone (PVP).

[0036] Preferably, the concentration of the sodium nitrite solution is 0.4-0.5 g / L, for example, it can be 0.4 g / L, 0.41 g / L, 0.42 g / L, 0.43 g / L, 0.44 g / L, 0.45 g / L, 0.46 g / L, 0.47 g / L, 0.48 g / L, 0.49 g / L or 0.5 g / L, etc.

[0037] Preferably, the molar ratio of sodium nitrite in the sodium nitrite solution to the total molar ratio of the nickel source, cobalt source, and manganese source is (2-5):(95-98), wherein the range of sodium nitrite (2-5) can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, or 5; and the range of the total molar ratio of the nickel source, cobalt source, and manganese source (95-98) can be, for example, 95, 95.5, 96, 96.5, 97, 97.5, or 98.

[0038] Preferably, the solvent in step (1) includes water.

[0039] Preferably, the alkaline solution in step (1) includes ammonia and / or sodium hydroxide solution.

[0040] Preferably, in the method for preparing the ternary precursor, the mixing is a stepwise mixing, which includes: first mixing the nickel source, cobalt source, manganese source and solvent once, and then mixing them a second time with sodium nitrite solution and alkaline solution.

[0041] Preferably, the temperature of the coprecipitation reaction in step (1) is 60-70℃, for example, it can be 60℃, 61℃, 62℃, 63℃, 64℃, 65℃, 66℃, 67℃, 68℃, 69℃ or 70℃.

[0042] Preferably, the pH value of the coprecipitation reaction in step (1) is 9-11, for example, it can be 9, 9.5, 10, 10.5 or 11.

[0043] Preferably, the coprecipitation reaction in step (1) is accompanied by stirring, and the stirring speed is 200-400 r / min, for example, it can be 200 r / min, 220 r / min, 240 r / min, 260 r / min, 300 r / min, 320 r / min, 340 r / min, 360 r / min, 380 r / min or 400 r / min, etc.

[0044] Preferably, the coprecipitation reaction time in step (1) is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.

[0045] Preferably, the calcination temperature in step (1) is 450-550℃, for example, it can be 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃ or 550℃, etc.

[0046] Preferably, the calcination time in step (1) is 4-6 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0047] Preferably, the calcination atmosphere in step (1) is an oxygen-containing atmosphere, and the gas in the oxygen-containing atmosphere includes, but is not limited to, oxygen.

[0048] Preferably, the mass ratio of the lithium manganese iron phosphate precursor, the ternary precursor, and the lithium source in step (2) is (0.6-0.8):(0.2-0.4):1, wherein the selection range of the lithium manganese iron phosphate precursor (0.6-0.8) can be, for example, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, or 0.8, etc., and the selection range of the ternary precursor (0.2-0.4) can be, for example, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, or 0.4, etc.

[0049] Preferably, the dysprosium source in step (2) includes dysprosium nitrate solution and / or dysprosium sulfate solution.

[0050] In one embodiment, the amount of dysprosium source added in step (2) is sufficient to completely wet the lithium manganese iron phosphate precursor, the ternary precursor, and the lithium source.

[0051] Preferably, the concentration of the dysprosium nitrate solution is 0.1-0.4 mol / L, for example, it can be 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L, 0.2 mol / L, 0.22 mol / L, 0.25 mol / L, 0.27 mol / L, 0.3 mol / L, 0.32 mol / L, 0.35 mol / L, 0.37 mol / L, or 0.4 mol / L, etc.

[0052] Preferably, step (2) further includes: between the mixing step and the sintering step, a grinding and drying step is performed sequentially.

[0053] Preferably, the grinding time is 5-7 hours, for example, 5 hours, 5.5 hours, 6 hours, 6.5 hours or 7 hours.

[0054] Preferably, the mixing in step (2) is a step-by-step mixing, which includes: firstly mixing the lithium manganese iron phosphate precursor, the ternary precursor and the lithium source, and then mixing them with the dysprosium source in a second stage.

[0055] Preferably, the secondary mixing method includes stirring, and the stirring speed is 200-400 r / min, for example, it can be 200 r / min, 220 r / min, 240 r / min, 260 r / min, 300 r / min, 320 r / min, 340 r / min, 360 r / min, 380 r / min or 400 r / min, etc.

[0056] Preferably, the secondary mixing time is 1-3 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.

[0057] Preferably, the temperature of the secondary mixing is 40-50℃, for example, it can be 40℃, 41℃, 42℃, 43℃, 44℃, 45℃, 46℃, 47℃, 48℃, 49℃ or 50℃, etc.

[0058] Preferably, the sintering in step (2) is stepwise sintering, which includes: first sintering and then sintering a second time.

[0059] In this invention, if only a second sintering is performed instead of a first sintering, the morphology and particle size of the material will be affected.

[0060] Preferably, the temperature of the first sintering is 250-350℃, for example, it can be 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃ or 350℃, etc.

[0061] Preferably, the sintering time is 5-7 hours, for example, 5 hours, 5.5 hours, 6 hours, 6.5 hours or 7 hours.

[0062] Preferably, the secondary sintering temperature is 600-700℃, for example, it can be 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃ or 700℃, etc.

[0063] Preferably, the secondary sintering time is 9-11 hours, for example, 9 hours, 9.5 hours, 10 hours, 10.5 hours or 11 hours.

[0064] Preferably, both the atmosphere for the primary sintering and the atmosphere for the secondary sintering are inert atmospheres, and the gases in the inert atmosphere include, but are not limited to, nitrogen.

[0065] Thirdly, the present invention provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery comprises the lithium manganese iron phosphate coated ternary composite material described in the first aspect.

[0066] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0067] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0068] This invention provides a ternary composite material coated with lithium manganese iron phosphate. The ternary core and the lithium manganese iron phosphate coating layer are integrated into the composite material, resulting in good homogeneous dispersion. At the same time, the doping of the rare earth element dysprosium into the ternary core and the lithium manganese iron phosphate coating layer not only solves the problems of poor conductivity and high self-discharge of pure lithium manganese iron phosphate, but also effectively improves the structural stability of the composite material by doping with the rare earth element dysprosium, enabling the composite material to exhibit excellent rate performance and cycle performance. Detailed Implementation

[0069] The technical solution of the present invention will be further illustrated below through specific embodiments.

[0070] Example 1

[0071] This embodiment provides a lithium manganese iron phosphate-coated ternary composite material. The composite material includes a ternary core and a lithium manganese iron phosphate coating layer covering the surface of the core. Both the ternary core and the lithium manganese iron phosphate coating layer are doped with dysprosium. The ternary core is a dysprosium-doped nickel-cobalt-manganese ternary cathode material. The mass ratio of the ternary core to the lithium manganese iron phosphate coating layer is 3:7. The thickness of the lithium manganese iron phosphate coating layer is 0.4 μm. The mass content of dysprosium in the lithium manganese iron phosphate coating layer is 2%, and the mass content of dysprosium in the ternary core is 2%.

[0072] This embodiment also provides a method for preparing a ternary composite material coated with lithium manganese iron phosphate, the preparation method comprising:

[0073] (1) Using MnSO4, FeSO4 and H3PO4 as raw materials, each material was weighed according to the molar ratio of Mn, Fe and P elements of 0.6:0.4:1, mixed evenly and pre-calcined at 300℃ in an argon-hydrogen mixed atmosphere (wherein the hydrogen content is 20%) for 2 hours to obtain lithium manganese iron phosphate precursor powder.

[0074] (2) Using Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Mn(CH3COO)2·4H2O as raw materials, a nickel-cobalt-manganese mixed salt solution was prepared by dissolving Ni, Co and Mn in deionized water at a molar ratio of 6:1:3. 0.45 g / L sodium nitrite solution was added to the mixed salt solution so that the molar ratio of sodium nitrite to the total molar ratio of the nickel, cobalt and manganese sources was 3:97. At the same time, 5 L of 10% ammonia water and 1 L of 1.5 mol / L sodium hydroxide solution were added. The solution temperature was controlled at 65℃, and the pH value was controlled at 10 using nitric acid solution. The mixture was stirred at 300 r / min for 2 h. After filtration and drying, the precipitate was calcined in an oxygen atmosphere at 500℃ for 5 h to obtain ternary precursor powder.

[0075] (3) The above-mentioned lithium manganese iron phosphate precursor, ternary precursor and lithium carbonate are mixed in a mass ratio of 0.7:0.3:1 to obtain a mixture. The mixture is added to a 0.3 mol / L dysprosium nitrate solution. The amount of dysprosium nitrate solution added is sufficient to completely wet the mixture. The mixture is stirred at 300 r / min for 2 h at 45 °C. The dispersed slurry is then put into a sand mill and ground for 6 h. The ground slurry is dried into powder using a pressure spray dryer. The powder is sintered at 300 °C for 6 h under a nitrogen atmosphere, and then sintered again at 650 °C for 10 h to obtain the lithium manganese iron phosphate coated ternary composite material.

[0076] Example 2

[0077] The difference between this embodiment and Example 1 is that the concentration of dysprosium nitrate solution in step (3) is adjusted to 0.1 mol / L, while the rest is exactly the same as in Example 1.

[0078] Example 3

[0079] The difference between this embodiment and Example 1 is that the concentration of dysprosium nitrate solution in step (3) is adjusted to 0.2 mol / L, while the rest is exactly the same as in Example 1.

[0080] Example 4

[0081] The difference between this embodiment and Embodiment 1 is that the concentration of dysprosium nitrate solution in step (3) is adjusted to 0.4 mol / L, while the rest is exactly the same as in Embodiment 1.

[0082] Example 5

[0083] This embodiment provides a lithium manganese iron phosphate-coated ternary composite material. The composite material includes a ternary core and a lithium manganese iron phosphate coating layer covering the surface of the core. Both the ternary core and the lithium manganese iron phosphate coating layer are doped with dysprosium. The ternary core is a dysprosium-doped nickel-cobalt-manganese ternary cathode material. The mass ratio of the ternary core to the lithium manganese iron phosphate coating layer is 2:8. The thickness of the lithium manganese iron phosphate coating layer is 0.2 μm. The mass content of dysprosium in the lithium manganese iron phosphate coating layer is 1%, and the mass content of dysprosium in the ternary core is 1%.

[0084] This embodiment also provides a method for preparing a ternary composite material coated with lithium manganese iron phosphate, the preparation method comprising:

[0085] (1) Using MnSO4, FeSO4 and H3PO4 as raw materials, weigh each material according to the molar ratio of Mn, Fe and P elements of 0.5:0.5:1, mix them evenly, and pre-calcine them in an argon-hydrogen mixed atmosphere (wherein the hydrogen content is 20%) at 250℃ for 3h to obtain lithium manganese iron phosphate precursor powder.

[0086] (2) Using Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Mn(CH3COO)2·4H2O as raw materials, a nickel-cobalt-manganese mixed salt solution was prepared by dissolving Ni, Co and Mn in deionized water at a molar ratio of 5:1:4. 0.4 g / L sodium nitrite solution was added to the mixed salt solution so that the molar ratio of sodium nitrite to the total molar ratio of the nickel, cobalt and manganese sources was 3:97. At the same time, 5 L of 10% ammonia water and 1 L of 1.5 mol / L sodium hydroxide solution were added. The solution temperature was controlled at 60℃, and the pH value was controlled at 9 using nitric acid solution. The mixture was stirred at 200 r / min for 3 h. After filtration and drying, the precipitate was calcined in an oxygen atmosphere at 450℃ for 6 h to obtain ternary precursor powder.

[0087] (3) The above-mentioned lithium manganese iron phosphate precursor, ternary precursor and lithium carbonate are mixed in a mass ratio of 0.6:0.2:1 to obtain a mixture. The mixture is added to a 0.2 mol / L dysprosium nitrate solution. The amount of dysprosium nitrate solution added is sufficient to completely wet the mixture. The mixture is stirred at 200 r / min for 3 h at 40 °C. The dispersed slurry is then put into a sand mill and ground for 5 h. The ground slurry is dried into powder using a pressure spray dryer. The powder is sintered at 250 °C for 7 h under a nitrogen atmosphere, and then sintered again at 600 °C for 11 h to obtain the lithium manganese iron phosphate coated ternary composite material.

[0088] Example 6

[0089] This embodiment provides a lithium manganese iron phosphate-coated ternary composite material. The composite material includes a ternary core and a lithium manganese iron phosphate coating layer covering the surface of the core. Both the ternary core and the lithium manganese iron phosphate coating layer are doped with dysprosium. The ternary core is a dysprosium-doped nickel-cobalt-manganese ternary cathode material. The mass ratio of the ternary core to the lithium manganese iron phosphate coating layer is 1:9. The thickness of the lithium manganese iron phosphate coating layer is 0.3 μm. The mass content of dysprosium in the lithium manganese iron phosphate coating layer is 3%, and the mass content of dysprosium in the ternary core is 3%.

[0090] This embodiment also provides a method for preparing a ternary composite material coated with lithium manganese iron phosphate, the preparation method comprising:

[0091] (1) Using MnSO4, FeSO4 and H3PO4 as raw materials, each material was weighed according to the molar ratio of Mn, Fe and P elements of 0.7:0.3:1, mixed evenly and pre-calcined at 350℃ in an argon-hydrogen mixed atmosphere (wherein the hydrogen content is 20%) for 1h to obtain lithium manganese iron phosphate precursor powder.

[0092] (2) Using Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Mn(CH3COO)2·4H2O as raw materials, a nickel-cobalt-manganese mixed salt solution was prepared by dissolving Ni, Co and Mn in deionized water at a molar ratio of 7:1:2. 0.5 g / L sodium nitrite solution was added to the mixed salt solution so that the molar ratio of sodium nitrite to the total molar ratio of the nickel, cobalt and manganese sources was 3:97. At the same time, 5 L of 10% ammonia water and 1 L of 1.5 mol / L sodium hydroxide solution were added. The solution temperature was controlled at 70℃, and the pH value was controlled at 11 using nitric acid solution. The mixture was stirred at 400 r / min for 1 h. After filtration and drying, the precipitate was calcined in an oxygen atmosphere at 550℃ for 4 h to obtain ternary precursor powder.

[0093] (3) The above-mentioned lithium manganese iron phosphate precursor, ternary precursor and lithium carbonate are mixed in a mass ratio of 0.8:0.4:1 to obtain a mixture. The mixture is added to a 0.4 mol / L dysprosium nitrate solution. The amount of dysprosium nitrate solution added is sufficient to completely wet the mixture. The mixture is stirred at 400 r / min for 1 h at 50 °C. The dispersed slurry is then put into a sand mill and ground for 7 h. The ground slurry is dried into powder using a pressure spray dryer. The powder is sintered at 350 °C for 5 h in a nitrogen atmosphere and then sintered again at 700 °C for 9 h to obtain the lithium manganese iron phosphate coated ternary composite material.

[0094] Example 7

[0095] The difference between this embodiment and embodiment 1 is that the concentration of dysprosium nitrate solution in step (3) is adjusted to 0.05 mol / L, so that the dysprosium content in both the ternary core and the lithium manganese iron phosphate coating layer is adjusted to 0.03%, while the rest is exactly the same as in embodiment 1.

[0096] Example 8

[0097] The difference between this embodiment and embodiment 1 is that the concentration of dysprosium nitrate solution in step (3) is adjusted to 0.5 mol / L, so that the dysprosium content in both the ternary core and the lithium manganese iron phosphate coating layer is adjusted to 4%, while the rest is exactly the same as in embodiment 1.

[0098] Example 9

[0099] The difference between this embodiment and embodiment 1 is that the step-by-step sintering in step (3) is adjusted to only perform two sinterings instead of one sintering, that is, only sintering at 650°C for 10 hours. The rest is exactly the same as in embodiment 1.

[0100] Example 10

[0101] The difference between this embodiment and embodiment 1 is that in step (2), sodium nitrite solution is not added to the mixed salt solution, but otherwise it is exactly the same as embodiment 1.

[0102] Comparative Example 1

[0103] The difference between this comparative example and Example 1 is that the dysprosium nitrate solution in step (3) is replaced with water, so that there is no dysprosium doping in the ternary core and the lithium manganese iron phosphate coating layer. Otherwise, it is exactly the same as Example 1.

[0104] Comparative Example 2

[0105] The difference between this comparative example and Example 1 is that in step (3), the ternary precursor is first added to the dysprosium nitrate solution, stirred and dried to obtain a ternary precursor doped with dysprosium; then the ternary precursor doped with dysprosium, the lithium manganese iron phosphate precursor and lithium carbonate are mixed, stirred, ground and sintered in sequence, so that only the ternary core of the composite material is doped with dysprosium, and the lithium manganese iron phosphate coating layer is not doped with dysprosium, and the rest is exactly the same as Example 1.

[0106] Comparative Example 3

[0107] This comparative example provides a method for preparing a ternary composite material coated with lithium manganese iron phosphate. The difference from Example 1 is that in step (3), the lithium manganese iron phosphate precursor is first added to a dysprosium nitrate solution, stirred and dried to obtain a lithium manganese iron phosphate precursor doped with dysprosium. Then, the lithium manganese iron phosphate precursor doped with dysprosium, the ternary precursor and lithium carbonate are mixed and stirred, ground and sintered in sequence, so that only the lithium manganese iron phosphate coating layer in the composite material is doped with dysprosium, and the ternary core is not doped with dysprosium. The rest is exactly the same as in Example 1.

[0108] Comparative Example 4

[0109] The difference between this comparative example and Example 1 is that the precipitate in step (2) is not calcined, but otherwise it is exactly the same as Example 1.

[0110] Performance testing

[0111] The composite positive electrode materials, acetylene black, and polyvinylidene fluoride (PVDF) provided in Examples 1-10 and Comparative Examples 1-4 were mixed in a mass ratio of 92%:4%:4% to prepare a slurry. The slurry was uniformly coated onto aluminum foil, vacuum dried at 110°C for 10 hours, and then the electrode sheet was compacted under a pressure of 20 MPa and cut into 14 mm diameter electrode sheets to obtain the positive electrode sheet. Subsequently, the above positive electrode sheets were used to assemble CR2032 coin cells in a glove box. The negative electrode was lithium metal, the separator was a Celgard 2400 polyolefin microporous membrane, and the electrolyte was 1 M LiPF6 dissolved in a mixed solvent of dimethyl carbonate (DMC), ethylene carbonate (EC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1. Electrochemical tests were performed on the battery using a blue electrode tester, specifically including:

[0112] (1) Initial specific capacity test: The battery was charged and discharged at 25℃±2℃. The charge and discharge test voltage was 2.5-4.2V, the charge and discharge current was 1.0C, and the 1C specific capacity of the positive electrode material was tested.

[0113] (2) 60-day self-discharge test: At 25±2℃, the battery is charged at 1C constant current and constant voltage to 4.2V and cut off at 0.02C. The battery is then stored continuously at 25℃ for 60 days. The cell voltage drop is measured after 60 days of storage.

[0114] (3) Rate performance test: Charge and discharge test was carried out at 25±2℃. The charge and discharge voltage was 2.5-4.2V, and the discharge current density was 1C and 5C respectively. The discharge capacity at 5C rate was calculated and divided by the discharge capacity at 1C rate. The larger the value obtained, the better the rate performance of the cathode material.

[0115] (4) Cyclic performance test: Under an environment of 25±2℃, the battery is charged at a constant current of 1C to a cutoff voltage of 4.2V, and then charged at a constant voltage until the current reaches 0.05C and charging is stopped. The battery is then left to stand for 30 minutes. The battery is discharged at a constant current of 1C to a cutoff voltage of 2.5V. The charge-discharge cycle is 100 cycles. The discharge capacity of the first cycle is recorded as E1, and the discharge capacity of the second cycle is recorded as E2. The ratio of E2 to E1 is the capacity retention rate after 100 cycles. The larger the retention rate, the better the cycle performance of the cathode material.

[0116] The test results are shown in Table 1.

[0117] Table 1

[0118]

[0119]

[0120] analyze:

[0121] As can be seen from the results of Examples 1-6, the lithium manganese iron phosphate coated ternary composite material provided by the present invention has high conductivity, and the corresponding battery exhibits high coulombic efficiency, high capacity, excellent rate performance and excellent cycle performance, and the battery has low self-discharge over 60 days.

[0122] A comparison of the results from Examples 1 and 7-8 shows that the concentration of dysprosium nitrate solution affects the dysprosium content in the ternary core and the lithium manganese iron phosphate coating layer. When the dysprosium content in the ternary core and the lithium manganese iron phosphate coating layer is too low, dysprosium cannot play a role in stabilizing the crystal structure of the cathode material, making it difficult to improve the first-efficiency of the composite material. When the dysprosium content in the ternary core and the lithium manganese iron phosphate coating layer is too high, excessive dysprosium will hinder lithium-ion insertion / extraction, increase the impedance of the material, and thus affect the first-efficiency, specific capacity, and capacity retention of the composite material.

[0123] A comparison of the results of Examples 1 and 9 shows that if only secondary sintering is performed in step (3) instead of primary sintering, the morphology of the material will be affected, and the material particle size will be larger, which will directly lead to a lower first-time efficiency and poor rate performance of the material.

[0124] As can be seen from the data of Examples 1 and 10, if sodium nitrite solution is not added to the mixed salt solution in step (2), it will affect the generated ternary precursor, thereby affecting the electrochemical performance of the lithium manganese iron phosphate coated ternary composite material, resulting in low initial efficiency and specific capacity, poor rate performance and cycle performance, and a large self-discharge of the battery in 60 days.

[0125] The results of Example 1 and Comparative Examples 1-3 show that when the ternary core and / or lithium manganese iron phosphate coating layer are not doped with the rare earth element dysprosium, the battery corresponding to the composite material exhibits lower coulombic efficiency, lower capacity, poorer rate performance, and poorer cycle performance, and the battery has a higher 60-day self-discharge. This indicates that doping the ternary core and lithium manganese iron phosphate coating layer with the rare earth element dysprosium is crucial.

[0126] The results of Example 1 and Comparative Example 4 show that if the precipitate is not calcined in step (2), the ternary precursor will have a large water content and the precursor will not have a fixed morphology, which is not conducive to the lithium-ion packing density of the material and affects the specific capacity and electrical performance of the cathode material.

[0127] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a ternary composite material coated with lithium manganese iron phosphate, characterized in that, The preparation method includes: (1) Prepare lithium manganese iron phosphate precursor and ternary precursor respectively: The method for preparing the ternary precursor includes: mixing a nickel source, a cobalt source, a manganese source, a solvent, and an alkaline solution, co-precipitating the mixture to obtain a precipitate, and calcining the precipitate to obtain the ternary precursor. (2) The lithium manganese iron phosphate precursor, the ternary precursor, the lithium source and the dysprosium source are mixed and sintered to obtain the lithium manganese iron phosphate coated ternary composite material; The composite material comprises a ternary core and a lithium manganese iron phosphate coating layer covering the surface of the core; the mass ratio of the ternary core to the lithium manganese iron phosphate coating layer is (0.1-0.3):(0.7-0.9); Both the ternary core and the lithium manganese iron phosphate coating are doped with dysprosium; the mass content of dysprosium in the lithium manganese iron phosphate coating is 1-3%; the mass content of dysprosium in the ternary core is 1-3%.

2. The preparation method according to claim 1, characterized in that, The ternary core comprises a nickel-cobalt-manganese ternary cathode material doped with dysprosium.

3. The preparation method according to claim 1, characterized in that, The thickness of the lithium manganese iron phosphate coating is 0.1-0.5 μm.

4. The preparation method according to claim 1, characterized in that, The method for preparing the lithium manganese iron phosphate precursor includes: mixing a manganese source, an iron source and a phosphorus source, and sintering to obtain the lithium manganese iron phosphate precursor.

5. The preparation method according to claim 4, characterized in that, In the method for preparing the lithium manganese iron phosphate precursor, the molar ratio of the manganese source, iron source and phosphorus source is (0.5-0.7):(0.3-0.5):

1.

6. The preparation method according to claim 4, characterized in that, In the method for preparing the lithium manganese iron phosphate precursor, the sintering temperature is 250-350℃.

7. The preparation method according to claim 4, characterized in that, In the method for preparing the lithium manganese iron phosphate precursor, the sintering time is 1-3 hours.

8. The preparation method according to claim 4, characterized in that, In the method for preparing the lithium manganese iron phosphate precursor, the sintering atmosphere is a reducing atmosphere.

9. The preparation method according to claim 1, characterized in that, In the method for preparing the ternary precursor, the molar ratio of the nickel source, cobalt source and manganese source is (5-7):1:(2-4).

10. The preparation method according to claim 1, characterized in that, In the method for preparing the ternary precursor, the mixed raw materials further include at least one of sodium nitrite solution, sodium persulfate solution, and polyvinylpyrrolidone.

11. The preparation method according to claim 10, characterized in that, The concentration of the sodium nitrite solution is 0.4-0.5 g / L.

12. The preparation method according to claim 10, characterized in that, The ratio of the molar amount of sodium nitrite in the sodium nitrite solution to the total molar amount of the nickel source, cobalt source and manganese source is (2-5):(95-98).

13. The preparation method according to claim 1, characterized in that, The solvent in step (1) includes water.

14. The preparation method according to claim 1, characterized in that, The alkaline solution in step (1) includes ammonia and / or sodium hydroxide solution.

15. The preparation method according to claim 10, characterized in that, In the method for preparing the ternary precursor, the mixing is a stepwise mixing, which includes: first mixing the nickel source, cobalt source, manganese source and solvent once, and then mixing them a second time with sodium nitrite solution and alkaline solution.

16. The preparation method according to claim 1, characterized in that, The temperature of the coprecipitation reaction in step (1) is 60-70℃.

17. The preparation method according to claim 1, characterized in that, The pH value of the coprecipitation reaction in step (1) is 9-11.

18. The preparation method according to claim 1, characterized in that, The coprecipitation reaction in step (1) is accompanied by stirring, and the stirring speed is 200-400 r / min.

19. The preparation method according to claim 1, characterized in that, The coprecipitation reaction in step (1) takes 1-3 hours.

20. The preparation method according to claim 1, characterized in that, The calcination temperature in step (1) is 450-550℃.

21. The preparation method according to claim 1, characterized in that, The calcination time in step (1) is 4-6 hours.

22. The preparation method according to claim 1, characterized in that, The calcination atmosphere in step (1) is an oxygen-containing atmosphere.

23. The preparation method according to claim 1, characterized in that, The dysprosium source in step (2) includes dysprosium nitrate solution and / or dysprosium sulfate solution; The concentration of the dysprosium nitrate solution is 0.1-0.4 mol / L.

24. The preparation method according to claim 1, characterized in that, Step (2) further includes: between the mixing step and the sintering step, a grinding and drying step is performed sequentially; The grinding time is 5-7 hours.

25. The preparation method according to claim 1, characterized in that, The mixing in step (2) is a step-by-step mixing, which includes: firstly mixing the lithium manganese iron phosphate precursor, the ternary precursor and the lithium source, and then mixing them with the dysprosium source in a second stage.

26. The preparation method according to claim 25, characterized in that, The secondary mixing method includes stirring, and the stirring speed is 200-400 r / min.

27. The preparation method according to claim 25, characterized in that, The secondary mixing time is 1-3 hours.

28. The preparation method according to claim 25, characterized in that, The temperature for the secondary mixing is 40-50℃.

29. The preparation method according to claim 1, characterized in that, The sintering in step (2) is stepwise sintering, which includes: first sintering and then sintering a second time.

30. The preparation method according to claim 29, characterized in that, The temperature for the first sintering is 250-350℃.

31. The preparation method according to claim 29, characterized in that, The sintering time for one sintering cycle is 5-7 hours.

32. The preparation method according to claim 29, characterized in that, The temperature for the secondary sintering is 600-700℃.

33. The preparation method according to claim 29, characterized in that, The secondary sintering time is 9-11 hours.

34. The preparation method according to claim 29, characterized in that, Both the atmosphere for the first sintering and the atmosphere for the second sintering are inert atmospheres.

35. A lithium-ion battery, characterized in that, The positive electrode of the lithium-ion battery contains a ternary composite material coated with lithium manganese iron phosphate prepared by any one of claims 1-34.

Citation Information

Patent Citations

  • A hybrid cathode material, a cathode sheet using the cathode material, and a lithium-ion battery.

    CN104300123B

  • Methods for preparing lithium manganese iron phosphate-carbon composite materials and lithium manganese iron phosphate-carbon composite materials

    CN110323434B

  • Doped and modified ternary positive electrode material and preparation method thereof

    CN103887483A

  • Ternary positive electrode material with core-shell structure, preparation method of ternary positive electrode material and lithium ion battery

    CN115692675A